Improving care coordination in community physical rehabilitation: A qualitative study of the change framework. (September 2019) - Symons, Jane L; Jamison, Julie; Dening, Jane; Murray, Linda; Pearson, Sue
Introduction: Contemporary rehabilitation change relies on effective collaboration and ongoing social interactions among stakeholders. The study objective was to explore the influence of the selected change framework and underlying social interactions during a care coordination improvement project. Methods: A qualitative study collected data from 35 employees in a community physical rehabilitation service. Participants were not only undergoing change to improve client care coordination but were also facilitating the change processes themselves. Symbolic interactionism guided the research design, and data were collected using interviews and observation. Blumer's six root beliefs were used for deductive data analysis and provided the framework for the findings. Results: Findings highlight that the perceptions of the selected change framework were mixed yet dynamic, with modification occurring via social interaction. Elements of Kotter's eight steps, lean thinking, and transformational change models were trialed. Implementation of the change processes required formal and informal group social interactions. Participants' different outlooks explained their mixed response to the change processes. Participants who supported the implemented changes believed the processes and outcomes were clear, appropriate, and inclusive. Time, energy, and positive social interactions enabled employees to drive change, with more of these resources desired to refine the vision, problem-solve implementation, and further improve care coordination. Discussion: This study enhances the understanding of how employees and the community physical rehabilitation service shaped each other during the change processes. The focus on social interactions highlights the slow rate of improved care coordination and need for increased resources and/or duration for successful change.